From global to regional perspective: unveiling Asia's human resource development trends through bibliometric lenses - Muhammad Aiman Arifin; Razlina Razali; Ummu Athilia Kamal (Cogent Business & Management, 2024)
Human Resource Development (HRD) has evolved tremendously since 1969, following the transition from an individual and organizational focus to a regional perspective. However, a comprehensive review of HRD specifically focused on the Asian region using bibliometric analysis has not been published. Given this gap, this bibliometric analysis utilized VOS Viewer, Bibliometric R-package, and Map Chart software to evaluate HRD-related publications originating from Asia, using data extracted from Scopus. The analysis involved nine indicators, including highly cited papers, influential authors, co-authorship patterns among countries, productive journals and nations, thematic mapping, emerging trends, keyword co-occurrence, bibliographic coupling, and related industries. The results showed that HRD in Asia is still undergoing development, with contributions from Asian scholars since 1984. As one of the pioneering regional bibliometric studies on HRD, this analysis provides insights to existing scholars, future researchers, and practitioners into HRD developments in Asia, while suggesting potential areas for future research advancement.
Keywords: 650; Human resource development; bibliometric analysis; VOS viewer; R-Package; map chart